Stop bridge collapse: a STEM activity about preventing corrosion of metals. (1st October 2020) - Yüceler, Ramazan; Aydın-Günbatar, Sevgi; Demirdöğen, Betül
Abstract: Integrated science, technology, engineering, and mathematics (STEM) approach has been implemented all around the world. STEM approach highlights the integration of different STEM disciplines, the use of daily-life problems, and engineering design process, which provides a context for students to learn knowledge of STEM disciplines and apply the knowledge in solving daily-life problems. In this activity, we focused on preventing corrosion with 12 th grade high school students (n = 28). A collection of newspaper articles was used to introduce the impact of corrosion on our lives and to attract students' attention to the problem. Then, a six-step engineering design process was followed to construct a small-scale model corrosion prevention method. Students worked in groups and studied on preventing corrosion. Results showed that the activity enriched students' understanding of the corrosion problem, its effect, and the methods preventing corrosion.